2019
DOI: 10.1155/2019/4959646
|View full text |Cite
|
Sign up to set email alerts
|

3-Deoxyglucosone Induces Glucagon-Like Peptide-1 Secretion from STC-1 Cells via Upregulating Sweet Taste Receptor Expression under Basal Conditions

Abstract: 3-Deoxyglucosone (3DG) is derived from D-glucose during food processing and storage and under physiological conditions. We reported that glucagon-like peptide-1 (GLP-1) secretion in response to an oral glucose load in vivo and high-glucose stimulation in vitro was decreased by acute 3DG administration. In this study, we determined the acute effect of 3DG on GLP-1 secretion under basal conditions and investigated the possible mechanisms. Normal fasting rats were given a single acute intragastric administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…This effect may be mediated by the increase of glucagon-like peptide 1 (GLP1) secretion. This is supported by the fact that, in glucose free conditions, 3-deoxyglucosone determines GLP1 secretion which is inhibited by lactisole (Song et al, 2019;Zhang et al, 2016). An investigation of fungiform and circumvallate papillae from rhesus macaques found that these cells can be classified in three subtypes based on the expression of TAS1Rs and their associated G-proteins.…”
Section: Reviews In Biological Andmentioning
confidence: 88%
“…This effect may be mediated by the increase of glucagon-like peptide 1 (GLP1) secretion. This is supported by the fact that, in glucose free conditions, 3-deoxyglucosone determines GLP1 secretion which is inhibited by lactisole (Song et al, 2019;Zhang et al, 2016). An investigation of fungiform and circumvallate papillae from rhesus macaques found that these cells can be classified in three subtypes based on the expression of TAS1Rs and their associated G-proteins.…”
Section: Reviews In Biological Andmentioning
confidence: 88%